Facile synthesis of ultrathin, undersized MoS2/graphene for lithium-ion battery anodes. Issue 102 (20th October 2016) - Chen, Lu; Yang, Yaqing; Gao, Yang; Tronganh, Nguyen; Chen, Fang; Lu, Mengna; Jiang, Yong; Jiao, Zheng; Zhao, Bing
Abstract : Ultrathin (∼5 layers), undersized (130–160 nm in size) MoS2 /graphene composites are fabricated by a facile acetic acid assisted hydrothermal route. Abstract : Ultrathin, undersized MoS2 /graphene composites are fabricated by a facile acetic acid assisted hydrothermal route and post-annealing. The structure and morphology characterization reveals that the MoS2 nanosheets with ∼5 layers and 130–160 nm in size are decorated on the surface of graphene nanosheets homogeneously and tightly. The effects of acetic acid and N -methyl-pyrrolidone solvent on the microstructures and electrochemical performances of the MoS2 /graphene composites are investigated. It is found that the acetic acid could maintain a constant pH and promote hydrolysis of thiourea, and thus many more MoS2 crystals nucleus were formed, while the N -methyl-pyrrolidone could inhibit the aggregation of the as-prepared MoS2 sheets, and therefore few-layered MoS2 sheets with a small size are obtained. Electrochemical tests confirmed that the lithium storage performance of ultrathin, undersized MoS2 /graphene is greatly improved compared to that without addition of acetic acid or N -methyl-pyrrolidone solvent. A high reversible capacity of 1229 mA h g −1 is achieved in the initial cycle and is maintained at 942.6 mA h g −1 after 50 cycles at a current density of 100 mA g −1 . Even at a current density of 1000 mA g −1, the reversible capacity could be maintained as high as 747 mA h g −1 .